Changes in Patient Satisfaction Scores During the Early COVID-19 Pandemic. (31st July 2021) - Maher, Dermot P; Hess, Demere; Edwards, Chevaune; Allen, Lisa
The coronavirus disease 2019 (COVID-19) pandemic has caused a rapid and widespread application of telemedicine services in the outpatient setting. Prior to COVID-19, patient satisfaction was measured with Consumer Assessment of Healthcare Providers and Systems (CAHPS) Clinician & Group Survey (CG-CAHPS) and was then measured with the Press Ganey telemedicine survey. Both surveys ask about a patient's likelihood to recommend a particular medical practice, which is a useful, but imperfect, surrogate for overall satisfaction. The purpose of this analysis was to identify any changes in patient satisfaction scores with the implementation of telemedicine services. A retrospective analysis of our institution's experience during the early months of the COVID-19 pandemic compared to the months immediately prior to the pandemic was conducted. The percent of patients with a "Top box" response to survey questions regarding their likelihood to recommend a medical practice were compared. A total of 14 430 CG-CAHPS results collected in November 2019 through February 2020 were compared to 22 009 telemedicine survey results collected between March and May 2020. In general, most medical specialties incorporated telemedicine but suffered a decrease in their patient's likelihood to recommend a medical practice during the first few months of the pandemic. However, the magnitude of this decrease was variable by medical specialty. Physical medicine and rehabilitation and pain medicine had relatively poor scores prior to the pandemic which did not statistically change. Oncology was the sole medical specialty that continued to have unchanged high patient satisfaction scores. These data provide insights for the refinement of telemedicine.